Pengaruh Kualitas Website Perpustakaan Universitas Jambi Terhadap Kepuasan Pengguna Menggunakan Metode WebQEM - Dewi Lestari; Daniel Arsa; Tania Rahmadesia (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2025)
Research uses the WebQEM technique, which assesses four factors: usability, functionality, reliability, and efficiency, to examine how the Jambi University library website quality affects user satisfaction. Eighty respondents completed questionnaires that were used to gather data. The findings demonstrate that, while there is room for improvement in a number of areas, including ease of help retrieval, page navigation, link validity, and information relevance, the quality of the library website has a positive and significant impact on user happiness. Users believe that the website is devoid of helpful features, navigates poorly, has broken links, and occasionally offers information that is insufficient for their needs. Enhancing navigation, adding help services, and assessing the accuracy of links and the suitability of the content are some suggestions for enhancement to the website.